Land of hope : Chicago, black southerners, and the great migration - Grossman, James R. (The University of Chicago Press, 1989)
"Grossman's rich, detailed analysis of black migration to Chicago during World War I and its aftermath brilliantly captures the cultural meaning of the movement." - Resumé vydavatele